Handbook of Nanoelectrochemistry Electrochemical Synthesis Methods, Properties, and Characterization Techniques - Aliofkhazraei, Mahmood; Makhlouf, Abdel Salam Hamdy; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This edited book is devoted to different electrochemical aspects of nano materials. This comprehensive reference text is basically divided in 3 parts: electrochemical synthesis routes for nanosized materials, electrochemical properties of nano materials and electrochemical characterization methods for nanostructures. The Handbook is a reference work to chemists and materials scientists interested in the nano aspects of electrochemistry. The chapters are written by a number of international experts in the field and the content will assist members of both electrochemical and materials communities to keep abreast of developments in the field.
Anodically Grown TiO2 Nanotube Membranes: Synthesis, Characterization and Application in Dye-Sensitized Solar Cells -- Application of Two-Dimensional Heisenberg Model to Electrochemical Nucleation Theory -- Bio-composite Nanomaterials for Electrochemical Biosensors -- Characterization of Metallic Micro(nano)cluster-Based Contacts for High-Effective Photovoltaic Devices -- Development of Nanostructures by Electrochemical Method for Chemical Sensors -- Electrochemical Control of the Core-Shell Cobalt-Platinum Nanoparticles -- Electrochemical Fabrication of Graphene-Based Nanomaterials -- Electrochemical Fabrication of Multi-Nano-Layers -- Electrochemical Fabrication of Nanostructures -- Electrochemical Preparation of Nanoresonators -- Electrochemical Sensors Based on Nanostructured Materials -- Electrochemical Synthesis of Metal Chalogenide Nanorods, Nanotubes, Segmented Nanorods and Co-axial Nanorods -- Electrochemically Fabricated Nanostructures in Energy Storage and Conversion Applications -- Electrodeposited Zn-Nanoparticles Composite Coatings for Corrosion Protection of Steel -- Electrodeposition of ZnO: Growth, Doping, and Physical Properties -- Electrodeposition to Produce Advanced Nanostructures for Electrochemical Capacitors -- Electroforming and Electrodeposition on Complex 3D Geometries: Special Requirements and New Methods -- Electroless Nanocomposite Coatings: Synthesis, Characteristics and Applications -- Electron Transfer and Charge Storage in Thin Films of Nanoparticles -- Electrophoretic Deposition (EPD): Fundamentals and Applications from Nano- to Micro-Scale Structures -- Formation and Characterization of Bimetallic Nanoparticles in Electrochemistry -- Formation and Characterization of Nanomaterials in Electrochemistry -- Frontiers of Nanoelectrochemistry and Application of Nanotechnology: A Vision for the Future -- Implementation of Nano-structured Catalysts in the Electrochemical Promotionof Catalysis -- Metal Oxide Nanoparticle Engineering for Printed Electrochemical Applications -- Microstructural Aspects of Ionic Conductivity in Nanocrystalline Zirconia -- Modelling of Metal Electrodeposition at the Nanoscale -- Nanomaterials in Analytical Bioelectrochemistry -- Nanomaterials Produced by Electrocrystallization Method -- Nanometerials in Solar Cells -- Nanoporous Anodic Aluminum Oxide: Fabrication, Characterization and Applications -- Nanoscale Electrodeposition of Metals and Semiconductors from Ionic Liquids Probed by Scanning Tunneling Microscopy -- Nanostructured Hybrid Graphene-Conducting Polymers for Electrochemical Supercapacitor Electrodes -- Nanostructured Transition Metal Oxides Produced by Electrodeposition for Application as Redox Electrodes for Supercapacitors -- New Approaches to the Study of Spinel Ferrite Nanoparticles for Biomedical Applications -- New Insights in Nano-electrodeposition: An Electrochemical Aggregative Growth Mechanism -- Plasmonic Nanostructured Supports for Spectro-Electrochemistry of Enzymes on Electrodes -- Porous Indium Phosphide: Preparation and Properties -- Recent Advances in Synthesis, Modification and Applications of TiO2 Nanotube Arrays by Electrochemical Anodization -- Recent Approaches for Designing Nanomaterials-Based Coatings for Corrosion Protection -- Scanning Electrochemical Microscopy: A Multiplexing Tool for Electrochemical DNA Biosensing -- Self-Assembled Functionalized Metallic Nanoparticles Template Toward Tailoring the Properties of Electrochemically Deposited Metallic Nanostructure -- Self-Assembled Monolayers on Nano-structured Composites for Electrochemical Sensing Applications -- Self-Assembled Peptide Nanostructures for the Development of Electrochemical Biosensors -- Self-Organized Nano- and Micro-structure of Electrochemical Materials by Design of Fabrication Approaches -- Self-Organized Nanostructures -- Synthesis, Modification and Characterization of Nanocarbon Electrodes for Determination of Nucleic Acids -- The Electrochemistry of Peptide Self-Assembled Monolayers -- Wet Chemical Approaches for Chemical Functionalization of Silicon and Titanium Nanomaterials.
Keywords: Electrochemistry; Nanoscience; Nanotechnology; Nanochemistry; Electrochemistry; Nanophysics; Nanotechnology; Nanochemistry